Fluctuations on Cash Flow Statements of Public Companies in Indonesia. - Astuty, Pudji; Priadana, Sidik; Estiningsih, Wening; Yuniarso, Yudi Budi (Abadi Institute, 2025)
This study aims to examine the effect of macroeconomic fluctuations on the cash flow statements of publicly listed companies in Indonesia. Using a panel data approach covering five public companies (AALI, UNVR, TLKM, ASII, and ICBP) over the period 2019–2023, the analysis employs the Common Effect Model (CEM). The independent variables include Gross Domestic Product (GDP), inflation rate, interest rate, and exchange rate, while the dependent variable is operating cash flow (CFO). Prior to estimation, classical assumption tests for multicollinearity and heteroskedasticity were conducted, confirming the validity and reliability of the model. The results indicate that GDP has a positive and significant impact on CFO, whereas inflation, interest rate, and exchange rate exert negative and significant effects. These findings suggest that macroeconomic conditions directly influence corporate liquidity and cash management. Companies need to implement proactive cash management strategies and hedging policies to mitigate risks associated with macroeconomic volatility. Furthermore, regulators should maintain economic stability to support corporate financial resilience. This study contributes to the empirical understanding of how macroeconomic variables affect corporate cash flows in emerging markets, particularly in Indonesia.